Flat-symmetric solutions in -αR^n gravity - Dzhunushaliev, V.; Nurtayeva, G.K.; Serikbolova, A.A. (Recent Contributions to Physics, 2019)
One of the most interesting and perspective directions in modern theoretical physics is studying of the modified gravity theories. The purpose of this direction is the description of gravitation within the modified theory so that without being in a conflict with the available experimental data to offer the best description of a wide range of the phenomena in cosmology, including, for the best understanding of the nature of dark matters and energy.In this work astrophysical objects are investigated: 4-dimensional domain walls and 6-dimensional thick branes in the modified theory of gravity. Regular asymptotically anti-de Sitter solutions in some range of value of the parameter n and δ were obtained. The main feature of these models consists in existence of a fixed point in phase space representing the center of a brane.
Keywords: modified theories of gravity; domain wall; thick brane